Political Trust in the “Places That Don't Matter” - McKay, Lawrence; Jennings, Will; Stoker, Gerry (Frontiers in Political Science, 2021)
A popular explanation for the recent success of right-wing populist candidates, parties and movements is that this is the “revenge of the places that don't matter”. Under this meso-level account, as economic development focuses on increasingly prosperous cities, voters in less dynamic and rural areas feel neglected by the political establishment, and back radical change. However, this premise is typically tested through the analysis of voting behavior rather than directly through citizens' feelings of political trust, and non-economic sources of grievance are not explored. We develop place-oriented measures of trust, perceived social marginality and perceived economic deprivation. We show that deprived and rural areas of Britain indeed lack trust in government. However, the accompanying sense of grievance for each type of area is different. Modeling these as separate outcomes, our analysis suggests that outside of cities, people lack trust because they feel socially marginal, whereas people in deprived areas lack trust owing to a combination of perceived economic deprivation and perceived social marginality. Our results speak to the need to recognize diversity among the “places that don't matter,” and that people in these areas may reach a similar outlook on politics for different reasons.